Good local governance: the criteria - Abou-hafs., Habiba; Fadila, Boutora (Archives of Business Research, 2018)
Local governance is generally derived from the power and capacity of local authorities to govern a territory in order to meet the needs of citizens. The general interest is consequently the strategic platform for local projects development. The art or way of governing is about how to implement a territorial development policy in consultation with the local actors involved. Local actors are required to master the processes and develop criteria for measuring good local governance. Associations, Citizens, State, Local Authorities, Networks of Associations and Non-governmental Organizations are all actors who play a very important role in local development. Good or bad local governance? What are the criteria for a good appreciation of local governance? The answer to these two questions requires a contextualization of the institutional system and its management. Good local governance uses behavioral values characterized by equity and social justice. An empirical study carried out in Agadir city on a representative sample of citizens shows the importance of the criteria of good local governance linked to the behavior of local actors.